AN ANALYSIS OF ERRORS OF THE USE OF ARTICLE IN DESCRIPTIVE TEXT - Bernieke Damanik; Joice Siadari; Agnes prianti; Bobby Pramjit Singh Dhillon (Merwinspy Publisher, 2023)
In learning English as a foreign language, writing is also an essential skill to be mastered. In Indonesia, writing has not become a culture. For the research design, the researcher used descriptive statistical analysis to attempt to describe and analyze the object by reality with instrument of collecting data is writing test and interview. Based on the finding and discussion in this research, the researcher can conclude that students in grade X IPA-1 of SMA Negeri 15 Medan who joined the writing test in this research still made errors in the use of English articles in descriptive text. There are three types of an error made by the student. The high frequency of error is an error of omission from 31 students; there are 113 or 55.3% errors of omission made by the student. Next is an error of misinformation from 31 students; there are 56 or 27.5% errors of misinformation made by the student. Last is the addition error from 31 students, with only 35 or 17.2% errors of addition made by the student.